PEMBENTUKAN KONTRAK MANAJEMEN HOTEL JARINGAN INTERNASIONAL DI BALI - Santi Dewi, Nyoman; Sukeni, Ni Nyoman; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
The development of the law of an international network of hotel management contracts in Bali has led to complex business transactions, causing a variety of problems. One factor is the difference in the legal system adopted by Indonesia with business partners that foreign nationals are invite dto collaborate. Giving rise to the existence of a worry and doubt in the implementation of the contract.
Keywords: Contracts, Hotel Management, International Networking